2017
DOI: 10.1152/jn.00245.2016
|View full text |Cite
|
Sign up to set email alerts
|

Independent coding of absolute duration and distance magnitudes in the prefrontal cortex

Abstract: Human behavioral studies have shown that spatial and duration judgments can interfere with each other. We investigated the neural representation of such magnitudes in the prefrontal cortex. We found that the two magnitudes are independently coded by prefrontal neurons. We suggest that the interference among magnitude judgments might depend on the goal rather than the perceptual resource sharing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 75 publications
0
23
0
Order By: Relevance
“…Brody, Hernández, Zainos, and Romo () suggested that the time‐dependent activity in PFC neurons encoded time itself and may be an intrinsic part of active memory maintenance mechanisms. A model of independent coding of absolute duration in the PFC has also been proposed (Marcos, Tsujimoto, & Genovesio, ). These studies support the idea, derived from neuroimaging and lesion studies, that some neurons in the PFC are involved in activity modulation that can distinguish among elapsed time intervals (Genovesio et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Brody, Hernández, Zainos, and Romo () suggested that the time‐dependent activity in PFC neurons encoded time itself and may be an intrinsic part of active memory maintenance mechanisms. A model of independent coding of absolute duration in the PFC has also been proposed (Marcos, Tsujimoto, & Genovesio, ). These studies support the idea, derived from neuroimaging and lesion studies, that some neurons in the PFC are involved in activity modulation that can distinguish among elapsed time intervals (Genovesio et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that estimates of surface are distinct from estimates of duration and number, but that duration and number may be more similar to one another. Indeed, neural recording studies in the prefrontal and parietal cortex of non-human primates have revealed overlapping, yet largely separate, representations of duration and size [49, 50], and number and size [51, 52], respectively. Further, while number, size, and time exhibit common activations of the right parietal cortex, they each engage larger networks of regions beyond this area [37, 53, 54].…”
Section: Discussionmentioning
confidence: 99%
“…The goal of the duration-discrimination task from Genovesio et al 30,47,48 is to compare the duration of two stimuli (S1 and S2) and select the stimulus that was presented for the longest duration. The RNN for this task has four inputs (S1, S2, go-cue for S1/S2 on left/right of screen, go-cue for S1/S2 on right/left of screen) and two outputs to indicate a hand response to either the right or left ( Figure M10).…”
Section: Methodsmentioning
confidence: 99%